Evidence of Adverse Selection in Iranian Supplementary Health Insurance Market - Mahdavi, Gh (Tehran University of Medical Sciences, 2012)
BACKGROUND: Existence or non-existence of adverse selection in insurance market is one of the important cases that have always been considered by insurers. Adverse selection is one of the consequences of asymmetric information. Theory of adverse selection states that high-risk individuals demand the insurance service more than low risk individuals do. METHODS: The presence of adverse selection in Iran’s supplementary health insurance market is tested in this paper. The study group consists of 420 practitioner individuals aged 20 to 59. We estimate two logistic regression models in order to determine the effect of individual’s characteristics on decision to purchase health insurance coverage and loss occurrence. Using the correlation between claim occurrence and decision to purchase health insurance, the adverse selection problem in Iranian supplementary health insurance market is examined. RESULTS: Individuals with higher level of education and income level purchase less supplementary health insurance and make fewer claims than others make and there is positive correlation between claim occurrence and decision to purchase supplementary health insurance. CONCLUSION: Our findings prove the evidence of the presence of adverse selection in Iranian supplementary health insurance market.